Plate tectonic aspects of the Triassic carbonate-hosted stratiform-stratabound base-metal deposits in the Western Balkan, NW Bulgaria - Irina Marinova; Zhelyazko Damyanov (Geologia Croatica, 2016)
The Triassic carbonate-hosted stratiform-stratabound base-metal deposits in the Western Balkan, NW Bulgaria, have well defined regional geological and tectonic settings, style ofmineralisation, mineralogical, geochemical and isotopic data. Their genesis, however, remains controversial in the framework of plate tectonic models, and is not supported by comparative analysis of possible counterpart candidates within the NW Tethyan domain. Besides, the crucial missing information is the geochronology of ore mineralisation relative to the Triassic carbonate host rocks. The article stresses the ambiguities due to the lack ofmineralisation age dating, and emphasises the necessity for building a convincing plate tectonic model based on the relevant geodynamic setting. A prospective direction of researchis the critical comparison with equivalent sediment-hosted base-metal deposits within the continental margin environments such as those in the Alps and Dinarides as well as others in the Alpine-Himalayan orogen and worldwide.